Linkage and Anti-Retroviral Therapy Within 72-hours at a Ryan White-Funded FQHC in the Deep South. (4th October 2017) - Halperin, Jason; Holm, Pam; Butler, Isolde; Conner, Katherine; Van Sickels, Nicholas
Abstract: Background: The Southern United States is disproportionately affected by HIV with the city of New Orleans ranking second for HIV incidence. Our clinic is committed to overcoming this disparity by optimizing the HIV care continuum. Recent studies have shown that immediate linkage to care and access to antiretroviral treatment improves the health of people living with HIV and has the added public health benefit of reducing HIV transmission. Our Ryan White-funded FQHC initiated a test-and-start strategy linking newly diagnosed patients with a treating provider and starting ART within 72 hours of HIV diagnosis. Methods: Patients newly diagnosed with HIV at one of our community based testing sites or by referral were linked to an ART-prescribing provider by a linkage to care specialist. Patients were assessed for readiness to begin ART and labs were drawn on day of visit. A 30-day supply of TAF/FTC and DTG are provided to patients and funded through Ryan White Part A in collaboration with our city's office of health policy. This regimen was chosen to overcome the risk of transmitted resistance. Patients were evaluated and enrolled in insurance services within this 30-day period. Results: Between December 2016 – March 2017, 35 patients were referred for rapid start. 32 patients were linked to care within 72 hours of diagnosis. The median age of patient was 26 with 81% identifying as male, 78% were MSM and 56% African-American. 75% were linked within 24 hours of diagnosis. 50% had a concurrent STI. 38% were uninsured. By 120 days post-diagnosis, 31/32 patients were virally suppressed with 78% within 60 days post diagnosis. 12/16 of the uninsured patients were enrolled in active insurance within 30 days and the remaining were enrolled in Ryan White Services. Conclusion: A test-and-start strategy of linkage and initiation of medications within 72 hours is feasible and highly effective in a Ryan-White funded clinic in the Southern United States. Disclosures: All authors: No reported disclosures.